Shoreline Change: Impact Of Sea Level Rise In South India – A Review - Galirajkumarreddy, S. Needhidasan and N. Subagunasekar (International Journal of Advanced Science and Technology, 2020)
Coastal zones are highly dynamic area of interaction between terrestrial and marine processes.  Beach front zones comprises about 10% of the land territory, these are thickly populated and supporting as much as 60% of the total populace. Shoreline change were brought about by disintegration, accumulation, sedimentation, examples of wind, wave and ocean level ascent. The whole stretch of the beach front zone along 7,500 km long coastline of India expect its significance due to high efficiency of its biological systems, misuse of normal assets, modern and port improvement, release of waste effluents and expanded the travel industry exercises. Numerous waterfront researchers have conveyed examine on breaking down and anticipating beach front changes. The need to predict and deal with the potential effect on coast requires precise examine on a micro level. The procedures of disintegration and accumulation are likewise connected with shoreline change. There are different strategies, models, and techniques accessible to discover the shoreline pointer, Digital shoreline investigation framework (DSAS). Programmed location, Remote detecting and GIS methods, topographic information assortment, and computerized picture preparing strategies presently make it feasible for the beach front agent to utilize target shoreline location techniques. Depending on the various resolution of satellite data results also varies. In this paper, an endeavor has been made to survey the strategies and systems which are utilized for shoreline change examination.